(untitled) (Praxis Educativa, 2026)
This article proposes an explanation for the relevance of designing expanded classrooms based on the arts. To this end, it draws on authors who occupy a central position in the field of education (Dewey, Greene, Camilloni, Litwin, Augustowsky, among others) and illustrates its point with a corpus of experiences involving teachers, students, and graduates of Literature and Arts. Throughout the article, it incorporates fragments of literary texts, culminating in a meta-analytical reflection on the practice of teaching, nature, and writing.